How do you normalize (2 i -3j -k)(2i−3j−k)?
1 Answer
Explanation:
To normalize a vector is to find unit vector (vector with magnitude/length of one) in the same direction as the given vector. This can be accomplished by dividing the given vector by its magnitude.
hatu=vecv/(|vecv|)ˆu=→v∣∣→v∣∣
Given
abs(vecv)=sqrt((v_x)^2+(v_y)^2+(v_z)^2)∣∣→v∣∣=√(vx)2+(vy)2+(vz)2
=>=sqrt((2)^2+(-3)^2+(-1)^2)⇒=√(2)2+(−3)2+(−1)2
=>=sqrt(4+9+1)⇒=√4+9+1
=>=sqrt(14)⇒=√14
We now have:
hatu=(<2,-3,-1>)/sqrt(14)ˆu=<2,−3,−1>√14
We can also rationalize the denominator for each of the components:
=>hatu=<(sqrt(14))/7,-(3sqrt(14))/14,-(sqrt(14))/14>⇒ˆu=<√147,−3√1414,−√1414>
Which may also be written
Hope that helps!